Endothelial Damage of the Portal Vein is Associated with Heparin-Like Effect in Advanced Stages of Cirrhosis - Shalaby, Sarah; Simioni, Paolo; Campello, Elena; Spiezia, Luca; Gavasso, Sabrina; Bizzaro, Debora; Cardin, Romilda; D'Amico, Francesco; Gringeri, Enrico; Cillo, Umberto; Barbiero, Giulio; Battistel, Michele; Zanetto, Alberto; Ruzzarin, Alessandro; Burra, Patrizia; Senzolo, Marco (Thrombosis and Haemostasis, 2020)
Background Portal vein thrombosis (PVT) is the most common thrombotic complication in cirrhosis; however, local risk factors involved in its pathogenesis are still not fully investigated. The aim of the study was to evaluate hemostasis and endothelial damage in the portal vein in patients with cirrhosis and portal hypertension.Methods Adult cirrhotics undergoing transjugular intrahepatic portosystemic shunt were consecutively enrolled. Rotational thromboelastometry (ROTEM), dosage of total circulating glycosaminoglycans (GAGs), and endotoxemia levels (lipopolysaccharide [LPS]), along with evaluation of endothelial dysfunction by quantification of circulating endothelial microparticles (MPs), were performed on citrated peripheric and portal venous blood samples from each enrolled patient.Results Forty-five cirrhotics were enrolled. ROTEM analysis revealed the presence of a significant heparin-like effect in portal blood (median ɑ angle NATEM 50° vs. HEPTEM 55°, p = 0.027; median coagulation time NATEM 665 s vs. HEPTEM 585 s, p = 0.006), which was not detected in peripheral blood, and was associated with a higher concentration of circulating GAGs. Even though total annexin V-MP circulating MPs were less concentrated in the splanchnic district, the proportion of MPs of endothelial origin, with respect to annexin V-MP, was significantly increased in the portal district (p = 0.036). LPS concentration was higher in portal (197 pg/mL) compared with peripheral blood (165 pg/mL) (p < 0.001).Conclusion Evidences of a damage of glycocalyx along with increased concentration of endothelial MPs suggest the presence of a significant endothelial alteration in the portal vein with respect to peripheral veins. Portal site-specific endothelial damage could hamper its antithrombotic properties and may represent an important local risk factor in the pathogenesis of PVT.
Keywords: heparin-like effect; microparticles; glycosaminoglycans; endotoxemia; portal hypertension